HLY1104 Winter Cruise Zooplankton Morphometrics - NSF Arctic Data Center (Arctic Data Center, 2014)
Zooplankton size data collected during the USCGC Healy cruise to the Chukchi, Beaufort, and Bering Seas in Nov. - Dec. 2011. See Readme file for methods.